High temperature resistant glass and preparation method thereof, glass preform and optical element

By adjusting the chemical composition of high temperature resistance glass, a stable glass network structure is formed, and the problem of disapproval of existing high -temperature resistance in high temperature environment has achieved low -cost, high -efficiency high -temperature -resistant glass preparation. Observe the window and photography equipment lens.

CN116282915BActive Publication Date: 2025-01-28QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310193933.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2025-01-28
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

Existing high-temperature resistant glasses are prone to crystallization and devitrification in high temperature environments, and have high production costs, making it difficult to meet the needs of high-temperature furnace observation windows and photography equipment lenses.

Method used

By adjusting the chemical composition of the glass, the relative content of Si4+, AL3+, Na+, K+, SN4+, CU2+and O2- is within a specific range, forming a glass network structure with high viscosity and stability, thereby suppressing the formation of crystal nuclei and crystalline crystals. Essence

Benefits of technology

The effect of long -term insulation and crystals between 1000 ° C and 1125 ° C, while reducing production costs, increasing the visible light through the glass and the transmission rate of near infrared areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116282915B_ABST
    Figure CN116282915B_ABST
Patent Text Reader

Abstract

The present invention discloses a high temperature resistant glass and a preparation method thereof, a glass preform and an optical element. In the present invention, the cation of the high temperature resistant glass contains 22.50 mol% to 23.25 mol% of Si in terms of cation molar percentage. 4+ , 7.39mol%~8.02mol%Al 3+ , 7.18 mol% to 7.71 mol% Na + , 0~0.55mol%K + , 0.05 mol% to 0.07 mol% Sn 4+ , 0.06mol%~0.12mol%Cu 2+ In terms of anion molar percentage, the anion of the high temperature resistant glass contains 61.23mol% to 61.60mol% of O 2‑ The melting temperature of the high temperature resistant glass material prepared by the present invention is much lower than that of quartz glass, and at the same time, it has a higher softening point temperature and stronger glass stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new glass materials, and in particular to high temperature resistant glass and a preparation method thereof, a glass preform and an optical element. Background Art

[0002] In industries such as ceramics and powder metallurgy, it is usually necessary to set an observation window on the door of a high-temperature furnace to view the sintering conditions in the furnace, and install photographic equipment near it to record the reaction progress of the materials in the high-temperature furnace in real time. This requires that the lens glass of the photographic equipment has both excellent visible light transmittance and heat resistance.

[0003] As is known to all, glass is a transparent inorganic non-metallic material. The main method for preparing large-sized blocks or flat glass is the "melting-cooling" method, that is, first, the glass batch is completely melted at high temperature, clarified and homogenized, and then formed and annealed. In the known glass system, quartz glass has good thermal shock resistance due to its unique glass structure, and the commonly used temperature is 1100°C to 1200°C. However, quartz glass is made by melting various pure natural quartz (such as crystal, quartz sand, etc.) at high temperature. The manufacture of quartz glass usually requires extremely high temperatures, which can reach more than 2000°C, which makes its production cost higher. In addition, quartz glass can also be prepared by synthesis, but the production efficiency of this type of method is low, resulting in further increase in production costs.

[0004] The difficulty in designing this type of high-temperature resistant lens glass lies in two aspects: on the one hand, it must not deform at high temperatures around 1000°C, which requires that the viscosity of the glass needs to be large enough, that is, the expansion softening point temperature should be higher than 1000°C; on the other hand, it must not become devitrified due to crystallization when kept at high temperatures for a long time, that is, strong glass stability is required.

[0005] In addition, when using CCD or CMOS image sensor equipment to shoot color scenes, it has a spectral sensitivity from the visible light region to about 1100nm. Since the "perception" of color by CCD or CMOS image sensors is different from that of the human eye, the infrared part that they can detect but the human eye cannot detect must be removed to make the color presented in the image consistent with the perception of the human eye. Therefore, it is generally necessary to "cut off" the near-infrared light, that is, to reduce the transmittance of the near-infrared light to achieve a high-definition effect.

[0006] So far, there is no report on high temperature resistant glass that can overcome the above defects. Summary of the invention

[0007] In order to make up for the deficiencies of the prior art, the present invention provides a high temperature resistant glass and a preparation method thereof, a glass preform and an optical element.

[0008] The present invention is achieved through the following technical solutions:

[0009] A high temperature resistant glass, wherein the cations of the high temperature resistant glass contain 22.50 mol% to 23.25 mol% of Si in terms of cation molar percentage. 4+ , 7.39mol%~8.02mol%Al 3+ , 7.18 mol% to 7.71 mol% Na + , 0~0.55mol%K + , 0.05 mol% to 0.07 mol% Sn 4+ , 0.06mol%~0.12mol%Cu 2+ In terms of anion molar percentage, the anion of the high temperature resistant glass contains 61.23mol% to 61.60mol% of O 2- In the above configuration, Si 4+ It is the main component of glass, that is, network forming ions. If Si 4+ If the content of Al is lower than 22.50 mol%, the glass viscosity is low and there is a tendency for crystallization when the temperature reaches 1000°C. If the content of Al is higher than 23.25 mol%, the glass is difficult to melt and clarify. 3+ It is a glass intermediate ion, Al 3+ In the glass, there are 4, 5 and 6 coordination, and the appropriate amount of Al 3+ The content is conducive to its existence mainly in the form of 4 coordination. 3+ When the content of Na is less than 7.39 mol%, the glass viscosity is low; when the content of Na is more than 8.02 mol%, the glass is difficult to melt and tends to crystallize at high temperature. + It is used to lower the melting temperature of glass and acts as an electrovalence balancing ion to promote the Al 3+ It exists in the form of [AlO4] tetracoordinate. If Na + If the mol% is lower than 7.18%, the glass viscosity will be too high. + If the mol% is higher than 7.71, the glass will tend to crystallize at high temperature. + It is used to lower the melting temperature of glass and acts as an electrovalence balancing ion to promote the Al 3+ It exists in the form of [AlO4] tetracoordinate, but if K + If the mol% is higher than 0.55%, the glass will tend to crystallize at high temperature. 4+ It plays a clarifying role in the glass melting process and is conducive to the discharge of bubbles in the glass melt. 4+ If the content is lower than 0.05 mol%, the clarification time will be longer. 4+ If the content of Cu is higher than 0.07mol%, the glass will tend to crystallize at high temperature. 2+In glass, it plays a role in absorbing near-infrared rays. If Cu 2+ If the content is less than 0.06 mol%, the effect of absorbing infrared rays is poor. 2+ If the content is higher than 0.12 mol%, the glass will tend to crystallize at high temperature. 2- In oxide glass, it mainly exists in [SiO4] tetrahedron and [AlO4] tetrahedron, that is, it mainly exists in the form of "bridge oxygen". 2- If the mol% is lower than 61.23%, the glass melt will have a high viscosity and will be difficult to melt. 2- When the content of non-bridging oxygen is higher than 61.60 mol%, the content of non-bridging oxygen increases and the glass tends to crystallize at high temperatures.

[0010] Preferably, Si 4+ The content is 22.60mol%~23.10mol%.

[0011] Preferably, Al 3+ The content is 7.52 mol% ~ 8.00 mol%.

[0012] Preferably, Na + The content is 7.45mol%~7.70mol%.

[0013] Preferably, K + The content is 0.00mol%~0.32mol%.

[0014] Preferably, Sn 4+ The content is 0.06mol%~0.07mol%.

[0015] Preferably, Cu 2+ The content is 0.08 mol% to 0.10 mol%.

[0016] Preferably, O 2- The content is 61.30mol%~61.52mol%.

[0017] A method for preparing high temperature resistant glass comprises the following steps: (1) according to the above chemical composition, accurately weighing the weight of the corresponding raw materials of each component and mixing them uniformly to prepare a batch material, melting and homogenizing the batch material in a high temperature furnace at 1700-1745°C; (2) casting the glass melt obtained in step (1) into a cast iron mold preheated at a temperature of 800-830°C, quickly transferring it to a muffle furnace for annealing for 1-2.5 hours, and then cooling it to room temperature.

[0018] Preferably, the raw materials used are silicon dioxide, aluminum oxide, sodium carbonate, potassium carbonate, tin dioxide and copper oxide.

[0019] A glass preform is made of the above-mentioned high temperature resistant glass.

[0020] An optical element is made of the above-mentioned high temperature resistant glass or the above-mentioned glass preform.

[0021] An optical instrument comprises the above optical element.

[0022] The present invention relates to a high temperature resistant glass material, the melting temperature of which is much lower than that of quartz glass, and the material has a higher expansion softening point temperature and stronger glass stability, so the present invention has the advantage of low energy consumption. In addition, the present invention relates to a high temperature resistant glass material, which can adjust the relative content of each cation by adjusting the glass composition, and induce Al 3+ It mainly exists in the glass in the form of [AlO4] coordination, which gives the glass a higher viscosity and inhibits the formation of crystal nuclei from both thermodynamic and kinetic aspects, that is, by inhibiting the formation of crystal nuclei in the glass to prevent its crystallization. Therefore, it will not crystallize and lose transparency even if it is kept warm for a long time between 1000°C and the upper limit temperature (that is, the expansion softening point temperature). In addition, the transmittance of the high-temperature resistant glass prepared in the present application in the near-infrared region of 780-1100nm is also relatively low, among which the transmittance of the high-temperature resistant glass prepared in the present application at 800nm ​​can be as low as 32%; the maximum visible light transmittance of the high-temperature resistant glass prepared in Examples 1 to 7 of the present application can reach up to 88%, and the upper limit temperature for long-term use can reach up to 1125°C; in addition, the high-temperature resistant glass of the present application does not have expensive raw materials in the preparation process, so the high-temperature resistant glass of the present application also has the advantages of low cost and easy availability of raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The X-ray diffraction pattern of the surface of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 1 after being kept at 1124° C. for 1000 hours;

[0024] Figure 2 The X-ray diffraction pattern of the surface of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 2 after being kept at 1122° C. for 1000 hours;

[0025] Figure 3 The X-ray diffraction pattern of the surface of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 3 after being kept at 1120° C. for 1000 hours;

[0026] Figure 4 The X-ray diffraction pattern of the surface of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 4 after being kept at 1118° C. for 1000 hours;

[0027] Figure 5The X-ray diffraction pattern of the surface of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 5 after being kept at 1125° C. for 1000 hours;

[0028] Figure 6 The X-ray diffraction pattern of the surface of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 6 after being kept at 1120° C. for 1000 hours;

[0029] Figure 7 The X-ray diffraction pattern of the surface of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 7 after being kept at 1118° C. for 1000 hours;

[0030] Figure 8 This is a transmittance curve of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 1 after being kept at 1124° C. for 1000 hours;

[0031] Fig. 9 This is a transmittance curve of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 2 after being kept at 1122° C. for 1000 hours;

[0032] Fig.10 This is a transmittance curve of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 3 after being kept at 1120° C. for 1000 hours;

[0033] Fig.11 This is a transmittance curve of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 4 after being kept at 1118° C. for 1000 hours;

[0034] Fig.12 This is a transmittance curve of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 5 after being kept at 1125° C. for 1000 hours;

[0035] Fig.13 This is a transmittance curve of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 6 after being kept at 1120° C. for 1000 hours;

[0036] Fig.14 This is a transmittance curve of the high temperature resistant glass with a thickness of 4.0 mm prepared in Example 7 after being kept at 1118° C. for 1000 hours. DETAILED DESCRIPTION

[0037] The following is a further description of a heat-resistant glass of the present invention through specific embodiments, wherein Embodiment 5 is the best embodiment. The composition table (mol%) of the heat-resistant glass of Embodiments 1 to 7 is shown in Table 1:

[0038] Table 1

[0039]

[0040] The upper limit temperature in Table 1 refers to the upper limit temperature for long-term use (i.e., expansion softening point temperature).

[0041] Embodiment 1:

[0042] According to the composition (cation mol%, anion mol%) of Example 1 shown in Table 1, 339.9 grams of silicon dioxide, 96.1 grams of aluminum oxide, 93.5 grams of sodium carbonate, 8.3 grams of potassium carbonate, 2.5 grams of tin dioxide and 1.2 grams of copper oxide were weighed respectively, and these raw materials were fully mixed, and then placed in a high-temperature ceramic crucible and kept at 1730°C for 5 hours to melt and homogenize, and then cast in a cast iron mold with a preheating temperature of 815°C, and quickly transferred to a muffle furnace and kept warm for 1 hour to eliminate internal stress, and then cooled to room temperature with the furnace to obtain a high-temperature resistant glass. The high-temperature resistant glass was ground and polished to obtain a high-temperature resistant glass with a thickness of 4.0 mm, and then the high-temperature resistant glass with a thickness of 4.0 mm was tested. The test found that the maximum transmittance in the visible light range, the transmittance at 800nm ​​and the upper limit temperature for long-term use (i.e., the expansion softening point temperature) are shown in Table 1.

[0043] Embodiment 2:

[0044] According to the composition of Example 2 shown in Table 1 (cation mol%, anion mol%), 335.3 grams of silicon dioxide, 97.8 grams of aluminum oxide, 97.2 grams of sodium carbonate, 8.5 grams of potassium carbonate, 2.4 grams of tin dioxide and 1.8 grams of copper oxide were weighed respectively, and these raw materials were fully mixed, and then placed in a high-temperature ceramic crucible and kept at 1715°C for 5 hours to melt and homogenize, and then cast in a cast iron mold with a preheating temperature of 810°C, and quickly transferred to a muffle furnace and kept warm for 1 hour to eliminate internal stress, and then cooled to room temperature with the furnace to obtain a high-temperature resistant glass. The high-temperature resistant glass was ground and polished to obtain a high-temperature resistant glass with a thickness of 4.0 mm, and then the high-temperature resistant glass with a thickness of 4.0 mm was tested. The test found that the maximum transmittance in the visible light range, the transmittance at 800nm ​​and the upper limit temperature for long-term use (i.e., the expansion softening point temperature) are shown in Table 1.

[0045] Embodiment three:

[0046] According to the composition of Example 3 shown in Table 1 (cation mol%, anion mol%), 331.8 grams of silicon dioxide, 99.3 grams of aluminum oxide, 98.7 grams of sodium carbonate, 9.3 grams of potassium carbonate, 2.4 grams of tin dioxide and 2.4 grams of copper oxide were weighed respectively, and these raw materials were fully mixed, and then placed in a high-temperature ceramic crucible and kept at 1710°C for 5 hours to melt and homogenize, and then cast in a cast iron mold with a preheating temperature of 800°C, and quickly transferred to a muffle furnace for 2 hours to eliminate internal stress, and then cooled to room temperature with the furnace to obtain a high-temperature resistant glass. The high-temperature resistant glass was ground and polished to obtain a high-temperature resistant glass with a thickness of 4.0 mm, and then the high-temperature resistant glass with a thickness of 4.0 mm was tested. The test found that the maximum transmittance in the visible light range, the transmittance at 800nm ​​and the upper limit temperature for long-term use (i.e., the expansion softening point temperature) are shown in Table 1.

[0047] Embodiment 4:

[0048] According to the composition (cation mol%, anion mol%) of Example 4 shown in Table 1, 334.6 grams of silicon dioxide, 100.7 grams of aluminum oxide, 100.6 grams of sodium carbonate, 2.1 grams of potassium carbonate, 2.3 grams of tin dioxide and 2.1 grams of copper oxide were weighed respectively, and these raw materials were fully mixed, and then placed in a high-temperature ceramic crucible and kept at 1700°C for 5 hours to melt and homogenize, and then cast in a cast iron mold with a preheating temperature of 800°C, and quickly transferred to a muffle furnace for 1.5 hours to eliminate internal stress, and then cooled to room temperature with the furnace to obtain a high-temperature resistant glass. The high-temperature resistant glass was ground and polished to obtain a high-temperature resistant glass with a thickness of 4.0 mm, and then the high-temperature resistant glass with a thickness of 4.0 mm was tested. The test found that the maximum transmittance in the visible light range, the transmittance at 800nm ​​and the upper limit temperature for long-term use (i.e., the expansion softening point temperature) are shown in Table 1.

[0049] Embodiment five:

[0050] According to the composition (cation mol%, anion mol%) of Example 5 shown in Table 1, 340.9 g of silicon dioxide, 96.4 g of aluminum oxide, 100.2 g of sodium carbonate, 2.3 g of tin dioxide and 1.8 g of copper oxide were weighed respectively, and these raw materials were fully mixed, and then placed in a high-temperature ceramic crucible and kept at 1745°C for 5 hours to melt and homogenize, and then cast in a cast iron mold with a preheating temperature of 830°C, and quickly transferred to a muffle furnace and kept warm for 1 hour to eliminate internal stress, and then cooled to room temperature with the furnace to obtain a high-temperature resistant glass. The high-temperature resistant glass was ground and polished to obtain a high-temperature resistant glass with a thickness of 4.0 mm, and then the high-temperature resistant glass with a thickness of 4.0 mm was tested. The test found that the maximum transmittance in the visible light range, the transmittance at 800 nm and the upper limit temperature for long-term use (i.e., the expansion softening point temperature) are shown in Table 1.

[0051] Embodiment six:

[0052] According to the composition of Example 6 shown in Table 1 (cation mol%, anion mol%), 344.1 grams of silicon dioxide, 92.8 grams of aluminum oxide, 96.5 grams of sodium carbonate, 3.4 grams of potassium carbonate, 2.1 grams of tin dioxide and 2.4 grams of copper oxide were weighed respectively, and these raw materials were fully mixed, and then placed in a high-temperature ceramic crucible and kept at 1745°C for 5 hours to melt and homogenize, and then cast in a cast iron mold with a preheating temperature of 825°C, and quickly transferred to a muffle furnace and kept warm for 2 hours to eliminate internal stress, and then cooled to room temperature with the furnace to obtain a high-temperature resistant glass. The high-temperature resistant glass was ground and polished to obtain a high-temperature resistant glass with a thickness of 4.0 mm, and then the high-temperature resistant glass with a thickness of 4.0 mm was tested. The test found that the maximum transmittance in the visible light range, the transmittance at 800nm ​​and the upper limit temperature for long-term use (i.e., the expansion softening point temperature) are shown in Table 1.

[0053] Embodiment seven:

[0054] According to the composition (cation mol%, anion mol%) of Example 7 shown in Table 1, 343.3 grams of silicon dioxide, 94.5 grams of aluminum oxide, 98.5 grams of sodium carbonate, 2.1 grams of potassium carbonate, 1.9 grams of tin dioxide and 1.2 grams of copper oxide were weighed respectively, and these raw materials were fully mixed, and then placed in a high-temperature ceramic crucible and kept at 1740°C for 5 hours to melt and homogenize, and then cast in a cast iron mold with a preheating temperature of 820°C, and quickly transferred to a muffle furnace for 2.5 hours to eliminate internal stress, and then cooled to room temperature with the furnace to obtain a high-temperature resistant glass. The high-temperature resistant glass was ground and polished to obtain a high-temperature resistant glass with a thickness of 4.0 mm, and then the high-temperature resistant glass with a thickness of 4.0 mm was tested. The test found that the maximum transmittance in the visible light range, the transmittance at 800nm ​​and the upper limit temperature for long-term use (i.e., the expansion softening point temperature) are shown in Table 1.

[0055] It can be seen from Table 1 that the maximum visible light transmittance of the high temperature resistant glass prepared in Examples 1 to 7 of the present application can reach up to 88%, the minimum transmittance at 800nm ​​can reach 32%, and the upper limit temperature for long-term use can reach up to 1125°C.

[0056] also, Figures 1 to 7 The X-ray diffraction patterns of the surfaces of the high temperature resistant glasses prepared in Examples 1 to 7 are shown respectively after long-term heat preservation for 1000 hours at their respective upper limit temperatures for long-term use (i.e., expansion softening point temperatures). Figures 1 to 7 It can be seen that Figures 1 to 7The diffraction peaks in are all diffuse, which indicates that the high temperature resistant glasses prepared in Examples 1 to 7 are still amorphous after being kept warm for 1000 hours at their respective upper limit temperatures for long-term use (i.e., expansion softening point temperatures), without any crystallization.

[0057] In addition, in order to verify that the high temperature resistant glass prepared in Examples 1 to 7 will not crystallize and lose transparency when kept warm for a long time at the upper limit temperature of long-term use (i.e., the expansion softening point temperature), the present application specifically places the high temperature resistant glass prepared in Examples 1 to 7 at the upper limit temperature of long-term use corresponding to each embodiment in Table 1 for 1000 hours, and then uses a spectrophotometer to detect the transmittance of the high temperature resistant glass prepared in Examples 1 to 7 after being kept warm for 1000 hours at the upper limit temperature of long-term use corresponding to each embodiment in Table 1. The test results are as follows: Figure 8-14 shown.

[0058] from Figure 8-14 It can be seen that after the high temperature resistant glasses prepared in Examples 1 to 7 were kept at their respective upper limit temperatures for 1000 hours, their maximum visible light transmittance and transmittance at 800 nm remained almost unchanged, that is, there was no decrease in transmittance due to crystallization.

[0059] Since the high temperature resistant glass prepared in the present application will not crystallize and lose transparency even if it is kept warm for a long time between 1000°C and the upper limit temperature (i.e., the expansion softening point temperature); and the transmittance of the high temperature resistant glass prepared in the present application is also relatively low at 780-1100nm, wherein the transmittance of the high temperature resistant glass prepared in the present application at 800nm ​​can be as low as 32%, therefore, the glass preform prepared using the high temperature resistant glass described in the present application also has the above advantages and is suitable for long-term use in high temperature environments.

[0060] In addition to being used to make glass preforms, the high temperature resistant glass described in the present application can also be directly used to make optical elements. Of course, the above-mentioned glass preforms can also be used to make optical elements, especially starting from the high temperature resistant glass prepared in the present application, to make optical elements such as lenses, prisms, and reflectors.

[0061] In addition, the present application also proposes an optical instrument, which has the above optical element. Therefore, by using the above optical element with excellent performance on the optical instrument, the applicability of the optical instrument with the above optical element for long-term use in a high temperature environment can also be effectively improved. Specifically, the optical instrument of the present invention can be an optical instrument that allows visible light to pass, such as a camera or a video camera.

Claims

1. A high temperature resistant glass, characterized in that: In terms of cation molar percentage, the cation of the high temperature resistant glass contains 22.60mol% to 23.10mol% of Si 4+ , 7.52mol%~8.00mol%Al 3+ , 7.18 mol%~7.71 mol% Na + , 0.00mol%~0.32mol%K + , 0.06mol%~0.07mol% Sn 4+ , 0.06mol%~0.12mol%Cu 2+ In terms of anion molar percentage, the anion of the high temperature resistant glass contains 61.23mol% to 61.60mol% of O 2- .

2. A method for preparing high temperature resistant glass, characterized in that: The following steps are involved: (1) According to the chemical composition of claim 1, the weight of the corresponding raw materials of each component is accurately weighed and mixed uniformly to form a batch material, and the batch material is melted and homogenized in a high-temperature furnace at 1700-1745°C; (2) The glass melt obtained in step (1) is cast into a cast iron mold preheated at a temperature of 800-830°C, quickly transferred to a muffle furnace for annealing for 1-2.5 hours, and then cooled to room temperature with the furnace.

3. The method for preparing high temperature resistant glass according to claim 2, characterized in that: The raw materials used are silicon dioxide, aluminum oxide, sodium carbonate, potassium carbonate, tin dioxide and copper oxide.

4. A glass preform, characterized in that: The glass preform is made of the high temperature resistant glass according to claim 1.

5. An optical element, characterized in that: The optical element is made of the high temperature resistant glass according to claim 1 or the glass preform according to claim 4.

6. An optical instrument, characterized in that: The optical instrument comprises the optical element according to claim 5 .

Citation Information

Patent Citations

  • Toughened glass and method for producing the same

    CN102015566A

  • Near infrared ray absorbing glass

    CN110612276A

  • Near infrared absorption filter glass with high refractive index

    CN112334422A

  • Tempered glass and glass for tempering

    US20160137550A1